INFLUENCE OF SERVICE QUALITY ON CUSTOMER LOYALTY THROUGH PERCEIVED RISK, SATISFACTION, AND TRUST IN BRANCHLESS BANKING CUSTOMERS - Aprilia, Nunung Eka (BISMA: Jurnal Bisnis dan Manajemen, 2021)
This study examines and analyses the effect of service quality on customer loyalty mediated by perceived risk, satisfaction, and trust variables in branchless banking customers. Today's lifestyle changes are strongly influenced by fintech, which is rapidly developing. There is a need for urban and remote communities to adapt with these changes. However, there are still many uneducated people, especially in remote areas. The method used in this quantitative research was conducted by distributing questionnaires and interviewing of 100 samples of branchless banking customers to explore all information about customers. Data processing was performed by using SEM PLS software. The results showed that service quality has a negative and significant effect on perceived risk; service quality has a positive and significant effect on satisfaction; service quality has a positive and significant effect on trust; perceived risk has a positive and significant effect on customer loyalty; satisfaction negatively and insignificantly affects customer loyalty; and trust has a positive and significant effect on customer loyalty. However, the effect of service quality on customer loyalty through perceived risk is negative and insignificant. Service quality on customer loyalty through satisfaction has a negative and insignificant effect. Meanwhile, the influence of service quality on customer loyalty through trust as a mediator variable is positive and significant. Keywords: Service quality, perceived risk, satisfaction, trust, customer loyalty, branchless banking.